Examining the Effects of Temperature on Recombination in Wheat - Coulton, Alexander; Burridge, Amanda J.; Edwards, Keith J. (Frontiers in Plant Science, 2020)
Recombination plays a crucial role in the generation of new varieties. The effectiveness of Recombination is limited by the distribution of crossover events, which in wheat and many other crops is skewed towards the distal regions of the chromosomes. Whole genome sequencing of wheat has revealed that there are numerous important genes in the pericentromeric regions, which are inaccessible to manipulation due to the lack of cross over events. Studies in barley have shown that the distribution of recombination events can be shifted towards the centromeres by increasing temperature during meiosis. Here we present an analysis of the effects of temperature on the distribution and frequency of recombination events in wheat. Our data show that although temperature does cause an inward shift in recombination distribution in some chromosomes, its overall utility is limited, with many genes remaining highly linked despite increases in environmental temperature during meiosis.